Self-Help and Black Firearm Crime - Ammons-Blanfort, Candice (Crime & delinquency, 2023)
Self-help theory posits that a negative perception of police engenders firearm violence rather than simply amplifying individuals? ownership of firearms for self-defense. A racially diverse police force may help decrease firearm use among Black citizens because marginalized groups in society often view a governmental institution as legitimate and impartial when the racial composition of the institution mirrors the population it represents. Analyses using multilevel data show that as the racial diversity of a city?s police department increases, Black criminal offenders are much less likely to use a firearm in an aggravated assault and in a violent crime. These findings buttress the claim that the institutional legitimacy of a police agency can be enhanced by descriptive racial representation.